Hedging with Futures: Does the Complex Model Beat the Simply Model When There is a Change in the Market Environment? - Jianru Fu, Xu Zhou, Cheng Xu (Forest Chemicals Review)
This paper investigates the difference in hedging performance between complex models and simple models when there is a change in the market environment from the perspective of model misspecification and estimation error. Dynamic VAR-DCC-GARCH models are constructed to represent complex models and static OLS, VAR, EC-VAR models are selected to represent simple models. Our main findings suggest that there is no significant difference in hedging performance between the simple model and the complex model within the sample (the period before the market environment changes). There is a decline in the out-of-sample performance of the two types of models, and the hedging efficiency of the complex model falls more than the simple model, its out-of-sample performance is inferior to the simple model.